Comprehensive Template for Enabling Environment Success and Failure Stories (V5.0 - IPSR + GenderUp Aligned) - CGIAR Science Program on Scaling for Impact (2025)
This template is designed to guide the documentation of experiences in developing, influencing, and strengthening enabling environments for scaling agrifood systems innovations. The objective is to communicate our experience to show that CGIAR can (and does) strengthen the enabling environment to achieve impact and scale. Stories should be told in a compelling narrative style, focusing on specific challenges, actors, and outcomes related to scaling. We encourage honest reporting on both successes and failures, framing failures as valuable opportunities for learning.